Answer:
yltkh
Step-by-step explanation:
ewgeg
Answer:
−y−1=3
Step-by-step explanation:
Which equation can be used to find the solution of (1/4)^y+1=64?
This can be solved by power of indices
(1/4)^(y+1)=64
(4^-1)^(y + 1)= 4^3
Note
(x^a)^b = x^ab
Hence:
4^(-1)(y + 1)= 4^3
4^-y - 1 = 4^3
Divide both sides by 4
−y−1=3
Hence, the equation that can be used to find the solution of (1/4)^y+1=64 is
−y−1=3
The "rule" being described here is nothing more than the input/output of a mathematical function.
<span>For every input 'x' value supplied, you only need to subtract three to it. For every input 'y' value, you only need to add four to it. </span>
<span>Example: I'll use variable 'm' to represent this function. Variable 'p' will represent the current input point. </span>
<span>m(p) = p[x - 3, y + 4] = p[-7 - 3, 0 + 4] = p[-10, 4]. 'p[]" is just the point.</span>